Evaluation of Carrot Pomace (Daucus carota L.) as Hypocholesterolemic and Hypolipidemic Agent on Albino Rats - Abd El-Moneim M.R. AFIFY; Ramy R.M ROMEILAH; Mahmoud M.H. OSFOR; Amir S.M. ELBAHNASAWY (Notulae Scientia Biologicae, 2013)
The current study examined the attenuating influence of dietary carrot pomace powder (CaPP) on hypercholesterolemia and various oxidative stress-associated with biochemical parameters in hypercholesterolemic rats. Thirty two male albino rats weighing 110±10 g were divided into four groups, the first group received the basal diet only and served as (negative control), the second group received the hypercholesterolemic diet and served as positive control, the other groups received hypercholesterolemic diet supplemented with 10%, 20% CaPP for six weeks. The obtained results revealed that groups supplemented with 10% and 20% CaPP significantly decrease total lipid, total cholesterol, triglycerides, low density lipoprotein cholesterol, liver enzymes: alanine aminotransferase, aspartate aminotransferase compared to positive and negative groups. Organs weight, body weight gain significantly decreased compared with positive control. Moreover dietary carrot pomace powder can used to reduce the body weight and reducing hypercholesterolemic complications. In addition, dietary carrot pomace powder serves to improve the blood picture and to reduce the blood glucose level in hypercholesterolemic rats and could use in obese people for body loss. Data of kidney function (Urea) record an increase in CaPP 20% level (26.9±2.96) but this increase was non significant with the negative control group (26.6±3.1).